Safety and efficacy of HK-660S in patients with primary sclerosing cholangitis: A randomized double-blind phase 2a trial - Woo Hyun Paik; Joo Kyung Park; Moon Jae Chung; Gunn Huh; Ce Hwan Park; Sang Hyub Lee; Heon Se Jeong; Hee Jin Kim; Do Hyun Park (Clinical and Molecular Hepatology)
Background/Aims A clinical unmet need persists for medications capable of modulating the progression of primary sclerosing cholangitis (PSC). This study aimed to assess the clinical feasibility of HK-660S (beta-lapachone) in PSC. Methods In this multicenter, randomized, double-blind, placebo-controlled, parallel-group phase 2 trial, participants were assigned in a 2:1 ratio to receive either 100 mg of HK-660S or a placebo twice daily for 12 weeks. The primary outcomes were the reduction in serum alkaline phosphatase (ALP) levels and the percentage of participants showing improvements in PSC severity, as determined by magnetic resonance cholangiopancreatography with the Anali score. Secondary endpoints included changes in liver stiffness and adverse events. Results The analysis included 21 patients, 15 receiving HK-660S, and six receiving a placebo. Improvements in the Anali score were observed in 13.3% of the HK-660S group, with no improvements in the placebo group. HK-660S treatment resulted in a 15.2% reduction in mean ALP levels, compared to a 6.6% reduction in the placebo group. A stratified ad-hoc analysis based on baseline ALP levels showed a statistically significant response in the HK-660S group among those with ALP levels greater than twice the upper limit of normal, with a 50% responder rate (P=0.05). Additionally, 26.7% of the HK-660S group showed improvements in the enhanced liver fibrosis score, with no improvements in the placebo group. HK-660S was generally well tolerated. Conclusions HK-660S is well tolerated among patients with PSC and may improve bile duct strictures, decrease serum ALP levels, and reduce liver fibrosis (cris.nih.go.kr, Number KCT0006590).